GILLNET SELECTIVITY ON CATLA CATLA (HAMILTON, 1822) IN ALIYAR RESERVOIR, TAMIL NADU, SOUTH INDIA - B. Sundaramoorthy; P. Parivallal; N. Neethiselvan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study undertaken on the gillnet selectivity of Catla catla at Aliyar Reservoir revealed that the optimum mesh size for the commercial exploitation of this species is 13.7 cm.  Among the gillnets presently being used, the usages of net A (mesh size 120 mm) is to be avoided to prevent the capture of immature and maturing animals.  The net B (mesh size 140mm) and Net C (mesh size 160 mm) were not found to pose any threat to the fishery.  The relationship between gilled girth(X) and fork length(Y) was found to be   Y = 1.19 + 0.73 X. The technical status of the gillnets of Aliyar reservoir need to be improved through correct attachment of floats and sinkers to enhance the catch efficiency of the nets.